Apollo/Three Nymph Denarii of Apollonia Illyriae - Macdonald , David (KOINON: The International Journal of Classical Numismatic Studies, 2024)
In 1908, Alfred Maier published “Die Silberprägung von Apollonia und Dyrrhachion,” cited here as Maier. His listings of the earlier Cow-and-Calf / Double Stellate Pattern drachms of Apollonia and the later Apollo / Nymphs coins have long been recognized as needing revision. Hasan Ceka, Monedhat e Dyrrahut e të Apollonisë (Tirana: Akademia e shkencave, 2008), cited here as Ceka, improved Maier’s lists, but his fullest treatment is available only in Albanian, so many readers continue to rely heavily on Maier’s work. Neither is completely satisfactory. Both omit some varieties, incorporate some earlier dubious readings, and list varieties in simple alphabetical order without any attempt to provide a chronological sequence of issues.